Pergaulan Positif Dalam Perspektif Alkitab - Waruwu, Nofedin (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The Community Service Program (Pengabdian Kepada Masyarakat or PKM) with the theme "Positive Fellowship from a Biblical Perspective" was conducted by Sekolah Tinggi Teologi Bethel The Way Jakarta. The program aimed to instill an understanding among students about the importance of building healthy, positive relationships based on biblical values. This activity targeted junior and senior high school students at Technosa School and employed methods such as material presentations, interactive discussions, positive fellowship simulations, and personal reflections. The materials emphasized principles of love, honesty, integrity, and the importance of setting boundaries in relationships. The results of the program showed an improvement in students' understanding of the importance of healthy and positive relationships, as well as an increased awareness of applying biblical values in daily life. The impact of this activity was evident in the more harmonious relationships among students, a more supportive social environment, and improved communication skills. This program is expected to be sustained through curriculum integration, mentorship, and collaboration with church communities and other schools.ABSTRAKKegiatan Pengabdian Kepada Masyarakat (PKM) dengan tema "Pergaulan Positif dalam Perspektif Alkitab" dilaksanakan oleh Sekolah Tinggi Teologi Bethel The Way Jakarta, dengan tujuan membentuk pemahaman siswa mengenai pentingnya membangun relasi yang sehat, positif, dan berlandaskan nilai-nilai Alkitab. Kegiatan ini menyasar siswa SMP dan SMA Technosa School, dengan metode yang meliputi sesi pemaparan materi, diskusi interaktif, simulasi pergaulan positif, dan refleksi pribadi. Materi yang disampaikan menekankan prinsip-prinsip kasih, kejujuran, integritas, serta pentingnya menjaga batasan dalam pergaulan. Hasil kegiatan menunjukkan peningkatan pemahaman siswa terhadap pentingnya pergaulan yang sehat dan positif, serta kesadaran untuk menerapkan nilai-nilai Alkitab dalam kehidupan sehari-hari. Dampak dari kegiatan ini terlihat pada hubungan antar siswa yang lebih harmonis, suasana pergaulan yang lebih mendukung, dan keterampilan komunikasi yang lebih baik. Kegiatan ini diharapkan dapat berkelanjutan melalui integrasi ke dalam kurikulum, pendampingan oleh mentor, serta kolaborasi dengan komunitas gereja dan sekolah lainnya.